Current Topics of Infectious Diseases in Japan and Asia - Tanaka, Kazuo.; Niki, Yoshihito.; Kokaze, Akatsuski. (Springer Japan, 2010)
This century may be called the era of infectious diseases, which are still the major cause of death in developing countries around the world. Focusing not only on such diseases as cholera, colitis, dengue, and bacterial intestinal infections, this book also addresses the current status of infectious diseases in Japan and Asiaparticularly, the new approaches to the H1N1 influenza pandemic and antibiotic-resistant pneumonia. One section covers the microbiological and social aspects of infectious diseases; another section discusses the epidemiology of infections such as tuberculosis and HIV/AIDS. Comprising the most up-to-date reports from prominent international researchers, the volume addresses the critical issues of today relating to clinical medicine, microbiology, and public health. A valuable and timely contribution to both the academic and medical fields, for scientists and practitioners alike, the work adds to the advancement of studies in infectious diseases.